2017
DOI: 10.1038/s41598-017-17270-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 Prevents Lymphoma in Drosophila

Abstract: Previous studies have established the anticancer effect of vitamin K2 (VK2). However, its effect on lymphoma induced by UBIAD1/heix mutation in Drosophila remains unknown. Therefore, we aimed to develop an in vivo model of lymphoma for the precise characterization of lymphoma phenotypes. We also aimed to improve the understanding of the mechanisms that underlie the preventative effects of VK2 on lymphoma. Our results demonstrated that VK2 prevents lymphoma by acting as an electron carrier and by correcting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 63 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Loss of function of heix or gain of function of Ras leads to an increased proliferation of hemocytes 19 , 45 . Hemocyte proliferation is closely correlated with the formation of melanotic mass, which can be attributed to an increase in the number of crystal cells associated with melanization 65 , 66 . Our study show that heix mutant leads to activation of Ras signaling on the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of function of heix or gain of function of Ras leads to an increased proliferation of hemocytes 19 , 45 . Hemocyte proliferation is closely correlated with the formation of melanotic mass, which can be attributed to an increase in the number of crystal cells associated with melanization 65 , 66 . Our study show that heix mutant leads to activation of Ras signaling on the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is reported that the melanotic mass formation in Drosophila is linked to a hemocyte-mediated immune response 64 . Previous studies report that loss of heix function not only activates the Ras signaling pathway but also leads to the activation of immune-related pathways (Toll, JAK/STAT, IMD pathways) 19 , 66 . Therefore, besides the Ras pathway, the formation of melanotic mass in heix mutants may be influenced by immune-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a synergy between vitamin D and vitamin K was necessary, thus necessitating the administration of vitamin K in severe COVID-19 patients prior to vitamin D supplementation [ 141 ]. Vitamin K was reported to have positive impacts in most cases of cancer and autoimmune diseases, which has been previously studied and reviewed [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ] and is summarized in Figure 5 . The emerging roles of vitamin K1 and K3 have also been noted due to the notable effects induced by this subclass of vitamins in regulation of tyrosine kinases and their downstream oncogenic pathways, as well as their regulatory effect on certain transcription factors [ 159 ].…”
Section: Impact Of Fat-soluble Vitamins In Covid-19 Prevention and Tr...mentioning
confidence: 99%
“…Heix (Heixuedian), is an orthologous protein of UBIAD1 in Drosophila melanogaster , composed of 359 amino acids with a molecular weight of 39.22 kDa ( 42 ). Following Heix mutation, a black dot phenotype lymphoma appeared in the 3rd to 4th instar larvae in Drosophila ( 49 , 50 ). UBIAD1 localizes at the mitochondria and converts vitamin K 1 to K 2 , which is a significant cofactor in eukaryotic blood coagulation and an electronic carrier binding to the cell membrane in bacteria ( 43 ).…”
Section: Subcellular Localization and Functions Of Ubiad1mentioning
confidence: 99%